(Re)conceptualizing Difference in the Context of the Acting Subject’s Identity - Anna Walczak (Lodz University Press, 2021)
What is the source and the effect of the acting subject’s identity? This question refers to difference, but not in its usual conceptualization, synonymous with a border and the need to maintain or transcend it. By reconceptualizing difference, which I see as “re-creating” the meaning and linking it with “added” meanings, this article restores its original load (importance) in being an acting subject, mediated in otherness. For this purpose, the différance of Jacques Derrida is invoked and his statements about it combined with those of other philosophers, in whom I found what is related and/or complementary and extends not only Derrida's thought, but that which constitutes the main theme of this article. On the one hand, otherness is an impulse to the “work” of the difference, and on the other hand, it is its effect. What is the role of the “work” of the difference in creating the identity of the acting subject? In connection with the “shift” of the effect of its work – otherness, into the area of the identity of the acting subject, can this subject say about itself: this is still me? In this context, what is responsive ethics, which, I believe, should be included in the contemporary humanistic and social discourse about the subject?